The Javanese People's Attitude towards Sundanese Language - Rahmawati, Septiani (2013)
The present study entitled The Javanese People's Attitude towards Sundanese Language aims to find out the Javanese people's attitude towards Sundanese language and their reasons to have such attitude. This research is a case study which involved five Javanese people working in a catering service company in Bandung as the respondents of the study. Data were collected from observations, questionnaires, and interviews. To analyze the data, some theories were applied; the theory proposed by Garret (2010) was utilized to analyze the components of language attitude that determine whether the attitude is positive or negative, whereas the theory from Holmes (2001) was employed to investigate the reasons why they have the attitude. Based on the data analysis result, it shows that the respondents tend to communicate in Sundanese language in their daily conversation. It also can be seen from the percentage of Sundanese language they used (28.06%) indicating that it is higher than the percentage of Javanese language used (3.96%). Regarding to the respondents' attitude towards Sundanese language, the findings refer that most of them have positive attitude due to their approval to use Sundanese language in their daily conversation. Penelitian ini berjudul The Javanese People's Attitude towards Sundanese Language yang bertujuan untuk mengetahui sikap orang Jawa terhadap bahasa Sunda dan alasan mereka untuk memiliki sikap seperti itu. Penelitian ini adalah studi kasus yang melibatkan lima orang Jawa yang bekerja di sebuah perusahaan jasa katering di Bandung sebagai responden dari penelitian. Data yang dikumpulkan dari pengamatan, kuesioner dan wawancara. Untuk menganalisa data, beberapa teori telah diterapkan; teori yang diusulkan oleh Garret (2010) digunakan untuk menganalisa komponen sikap bahasa yang menentukan apakah sikap tersebut adalah positif atau negatif, sedangkan teori dari Holmes (2001) digunakan untuk menyelidiki alasan mengapa mereka memiliki sikap tersebut. Berdasarkan hasil data analisis, ditemukan bahwa para responden cenderung berkomunikasi dengan menggunakan bahasa Sunda dalam percakapan sehari-hari mereka. Hal tersebut dapat dilihat dari persentase bahasa Sunda yang mereka gunakan (28.06%) menunjukkan bahwa itu lebih tinggi daripada persentase bahasa Jawa yang digunakan (3,96%). Mengenai sikap responden terhadap bahasa Sunda, temuan merujuk bahwa kebanyakan dari mereka memiliki sikap positif karena persetujuan mereka untuk menggunakan bahasa Sunda dalam percakapan sehari-hari. Kata Kunci: Jawa, Sikap, Bahasa Sunda.